Molecular hydrogen protects against ischemia-reperfusion injury in a mouse fatty liver model via regulating HO-1 and Sirt1 expression - Shaowei Li (Nature Portfolio, 2018)
Abstract Fatty liver has lower tolerance against ischemia-reperfusion (I/R) injury in liver operations, including liver transplantation. Seeking to ameliorate liver injury following I/R in fatty liver, we examined the protective effect of hydrogen (H2) saline on I/R liver injury in a methionine and choline-deficient plus high fat (MCDHF) diet-induced fatty liver mouse model. Saline containing 7 ppm H2 was administrated during the process of I/R. Livers were obtained and analyzed. Primary hepatocytes and Kupffer cells (KCs) were obtained from fatty liver and subjected to hypoxia/reoxygenation. Apoptosis-related proteins and components of the signaling pathway were analyzed after treatment with hydrogen gas. The MCDHF I/R group showed higher levels of AST and ALT in serum, TUNEL-positive apoptotic cells, F4/80 immunopositive cells, mRNA levels of inflammatory cytokines, constituents of the signaling pathway, pro-apoptotic molecules in liver, and KCs and/or primary hepatocytes, compared to the control group. In contrast, H2 treatment significantly suppressed the signs of I/R injury in fatty liver. Moreover, the expression of Bcl-2, HO-1, and Sirt1 in liver, KCs, and hepatocytes by hydrogen gas were increased, whereas caspase activation, Bax, and acetylation of p53 were suppressed by hydrogen gas. These results demonstrated that H2 treatment ameliorated I/R liver injury in a fatty liver model by reducing hepatocyte apoptosis, inhibiting macrophage activation and inflammatory cytokines, and inducing HO-1 and Sirt1 expression. Taken togather, treatment with H2 saline may have a protective effect and safe therapeutic activity during I/R events, such as in liver transplantation with fatty liver.